Hunter-gatherer specialization in the late Neolithic of southern Vietnam – The case of Rach Nui. (30th September 2018) - Castillo, Cristina Cobo; Fuller, Dorian Q.; Piper, Philip J.; Bellwood, Peter; Oxenham, Marc
Abstract: Rach Nui is a late Neolithic settlement of hunter-gatherers in southern Vietnam. However, the site also has a series of mortared floors corresponding to a sedentary lifestyle, where the inhabitants continued to live in the same area and repaired or replaced their floors over a period of 150 years. The inhabitants relied on a mixed economy that included domesticated and gathered plants, as well as hunted and managed animals. Although, there is evidence for the consumption of domesticated rice and foxtail millet, the inhabitants were mainly hunter-gatherers who relied on their surrounding mangrove and swamp forest habitats for most of their food requirements. From the archaeobotanical work done, it appears that the domesticated cereals, rice and foxtail millet, found at the site were imported. On the other hand, sedge nutlets and parenchyma were identified in high frequencies and were probably locally sourced, suggesting that foraging and/or vegeculture played a major role in the economy of Rach Nui.